Create stunning renders using V-Ray in 3ds Max : guiding the next generation of 3D renderers - Nikita, Margarita (CRC Press, 2021)
Create Stunning Renders using V-Ray in 3ds Max: Guiding the Next Generation of 3D Renderers is a step-by-step guide on how to create realistic renderings using V-Ray in 3ds Max. The potentials of V-Ray are detailed using a bedroom scene as an example. The book introduces the 3ds Max interface and the basic commands, allowing readers to familiarize themselves with the work environment from the very beginning. This book is intended for architects, interior designers, and anyone else wanting to create photorealistic renderings using V-Ray in 3ds Max. The reader does not need experience to follow this book, but any prior knowledge of working in 3ds Max will help the reader jump right in. Margarita Nikita is the co-founder of High Q Renders LLC, an award-winning creative company based in San Francisco, CA, with offices in Greece. Nikita has published several design books on 2D and 3D graphic design, some of which are used in university courses, actively contributing to the formation of the new generation of 3D modelers in her native country, Greece. She shares her knowledge, advice, and tips and tricks on her YouTube channel, Margarita Nikita. More of her work is available at her Instagram account, @ margarita.nikita.